Radiographic findings and clinical factors in dogs with surgically confirmed or presumed colonic torsion. Issue 3 (23rd January 2018) - Gremillion, Christine L.; Savage, Mason; Cohen, Eli B.
Abstract: Colonic torsion is a life‐threatening condition in dogs and radiographic findings for this condition have not been well described. The purpose of this retrospective case series was to describe radiographic findings and clinical signs in a group of dogs with colonic torsion. Inclusion criteria were dogs presenting during the period of 2006 and 2016, and that had abdominal radiography and a surgically confirmed or presumed diagnosis of colonic torsion. For each dog, clinical data were recorded from medical records and imaging findings were recorded from retrieved plain radiographs and positive contrast radiographs in which barium enema was performed. Fourteen dogs met inclusion criteria. Of these, nine dogs had colonic torsion confirmed at surgery, with five dogs having surgical confirmation of colonic congestion or mesenteric torsion. Radiographic findings included segmental distention of the colon (14/14), focal narrowing of the colon (11/14), displacement of cecum (11/14), displacement of descending colon (14/14), and mild to no small intestinal distention (14/14). In cases where barium enema was performed, focal narrowing of the colon and longitudinal striations that course in a helical pattern were identified, termed the "torsion sign." Vomiting was the most common clinical sign observed (12/14), followed by abdominal pain in a small majority of cases (8/14). Severe abdominal pain and hypovolemic shock were uncommon in the patients reported (3/14). Colonic torsion should be considered as a differential diagnosis for dogs with radiographic segmental colonic distention with displacement of the descending colon and cecum. Barium enema is recommended for more definitive diagnosis.